PENGEMBANGAN MODEL PEMBELAJARAN KEWIRAUSAHAAN BERBASIS KEARIFAN LOKAL (ENCENG GONDOK) UNTUK MENINGKATKAN MINAT BERWIRAUSAHA PADA MAHASISWA UNIVERSITAS ACHMAD YANI BANJARMASIN - Maria Ulfah; Dewy Nurchaifa Pebriany (Cangkal : Jurnal Ilmu Sosial Dan Humaniora, 2025)
Students' entrepreneurial interest is a crucial factor in producing independent university graduates capable of creating jobs. However, entrepreneurship learning in universities still tends to be theoretical and lacks contextualization with local potential. This study aims to develop an entrepreneurship learning model based on the local wisdom of water hyacinth and to test its feasibility and effectiveness in increasing entrepreneurial interest at Achmad Yani University, Banjarmasin. This study employed a Research and Development (R&D) method, with the stages of needs analysis, model design, development, expert validation, and limited trials. The subjects were students taking entrepreneurship courses. Data collection techniques included questionnaires, observations, and interviews. The results showed that the developed learning model was deemed feasible by subject matter experts and learning experts and effective in increasing students' entrepreneurial interest. This model is able to integrate the potential of local wisdom into contextual, applicable learning, and oriented towards real-life entrepreneurial experiences.